Principles of controlling intersystem power flows in the conditions of the electricity market - Yusifbayli Nurali; Alizade Rana (E3S Web of Conferences)
The principles of electricity market control in relation to intersystem communications is analyzed in the paper. Electricity market can be both intersystem communications and legal entities of transmission and distribution networks of power systems. As an example, parallel operation of two power systems through the intersystem communication with different operating costs was considered.